DOCTRINAL FOUNDATIONS OF DEMOCRATIC TRANSFORMATIONS IN MODERN CHINA: A CASE STUDY OF CONFUCIANISM - A. A. Savtyireva; Y. G. Efimov (Гуманитарные и юридические исследования)
The aim of the paper is to examine the influence of the Confucian doctrine on democratic processes in modern China. The authors have studied the role of Confucianism in Chinese political processes in different historical periods, as well as its relationship with the processes of democratization and modernization; a degree of its compatibility with the principles of democracy, the presence of democratic traits in it.